Dual step irradiation process for in situ generation and patterning of silver nanoparticles in a photocured film. Issue 18 (4th February 2016) - Roppolo, I.; Doriguzzi Bozzo, A.; Castellino, M.; Chiappone, A.; Perrone, D.; Bejtka, K.; Bocchini, S.; Sangermano, M.; Chiolerio, A.
Abstract : Novel dual step irradiation process for the in situ generation and patterning of silver nanoparticles in a photocured matrix was developed. Abstract : The realization of nanocomposite materials with topologically tailored composition and functional properties represents an important technological challenge for many applications such as optics and electronics. In the last years a great effort has been devoted to develop techniques that, by controlling the generation and the distribution of nanoparticles, allow the realization of structured metal/polymer nanocomposites. In this work we present a novel methodology for the realization of patterned silver/polymer nanocomposites generated in a polymeric matrix starting from a single formulation exploiting a fully photoinduced dual wavelength method, maintaining control over size distribution, with a straightforward influence on electronic/plasmonic/photonic properties. A step by step study of the process was carried out, investigating both the polymerization kinetics and the nanoparticles generation. Finally patterning in the polymeric matrix was performed through photolithographic technology and a washing process was developed in order to stabilize the material toward ageing. This technique opens new perspectives in the realization of multifunctional materials and devices exploiting electronic/plasmonic/photonic properties of the embedded nanoparticles and it is envisaged to be further improved by applying region-selective techniques.